Movement ecology of the bronze whaler shark (carcharhinus brachyurus) in southern Africa - Rogers, Toby (Department of Biological Sciences, 2025)
Coastal marine ecosystems are functionally important for many species of shark including large wide-ranging species that occupy elevated trophic positions. Ecological or anthropogenic perturbations that alter the abundance, distribution or movements of large sharks can thus have destabilising ecosystem impacts along economically important coastal regions. The bronze whaler shark (Carcharhinus brachyurus) is a vulnerable carcharhinid, with a global distribution, largely restricted to temperate coastal waters. In southern Africa, they are exploited by several commercial and recreational fisheries and have become increasingly important for ecotourism. However, despite having a well- studied general biology and diet, the movement ecology of C. brachyurus at regional and fine scales is poorly understood, limiting interpretations of the species' response to current and future anthropogenic or ecological stressors. In this thesis I used long-term conventional tagging records (n >10000) to generate a broadscale (transboundary and regional) understanding of their spatiotemporal distribution, occurrence and movement in southern Africa. Additionally, 73 C. brachyurus were acoustically tagged to explore how environmental (season and water temperature), and trophic (prey and top predator occurrence) variables may influence the movements C. brachyurus at both regional and local scales (i.e., within False Bay) in South Africa. Transboundary movement of conventionally tagged C. brachyurus between South Africa, Namibia and Angola supported the lack of geographical variation in the genetics of the southern Africa population. The south coast of South Africa represented a potentially important nursery region, with juveniles largely absent from Namibia and Angola. The low frequency of transboundary movement (n= 3) and no evidence of juvenile movement between South Africa and Namibia suggests parturition and juvenile habitat may be regionally discrete. Clear seasonal patterns of occurrence were evident for all life stages in South Africa, with sharks typically distributed in warm-temperate south coast regions during the austral summer and an increase in subadult and adult occurrence in subtropical east coast waters during winter. Acoustically tagged subadults and adults showed similar patterns of seasonal occurrence which correlated positively with warmer surface water temperatures. Evidence of repeat annual movements of acoustically tagged sharks between warm-temperate and subtropical regions, which spatiotemporally overlapped with the winter eastward migration of their prey (Sardinops sagax), suggests subadult and adult C. brachyurus may actively track this prey source along their eastward migration in South Africa. The lack of juveniles partaking in this migration event could also provide evidence of an ontogenetic shift in migratory behaviour. Within False Bay, the declining temporal occurrence trend of Carcharodon carcharias, corresponded with an increase in C. brachyurus at several C. carcharias aggregation sites. Tracking of C. brachyurus showed higher use of biologically productive, low visibility north and north-eastern inshore regions, contrasting the north-western and northern inshore habitat use of C. carcharias during summer. While this was suggestive of fine-scale horizontal habitat partitioning, long-term catch records of conventionally tagged C. brachyurus in higher risk C. carcharias habitat indicates the two species may spatially overlap at finer scales (i.e., depth). Site fidelity was apparent for several sharks which returned seasonally to False Bay after their eastward winter migration, but the immigration of sharks tagged at other South African sites was low (i.e., four out of 53). Thus, the increase in occurrence of C. brachyurus at sites historically dominated by C. carcharias is unlikely to reflect recent immigration but rather a behavioural release from the top-down effects of a larger predator following the rapid decline in the latter's presence in False Bay. The slow life-history traits, affinity to coastal regions and cross-border movements leave the southern African C. brachyurus population vulnerable to overexploitation in the absence of regionally aligned research and management. Furthermore, climate change is predicted to disrupt the seasonal migration of an important prey source which may have direct fitness-level effects and wider ecosystem implications. Understanding how both anthropogenic and ecological changes may impact ecologically important large predator populations requires foundational knowledge of both their spatial ecology and trophic interactions, both of which have been advanced in this thesis.